THE EFFECT OF PBL LEARNING MODEL ON THE FIFTH-GRADE STUDENTS’ MATH ARITHMETICAL SKILLS AT MIS PERDAMEAN SIGAMBAL - Leli Hasanah Lubis; Mhd. Rafi’i Ma’arif Tarigan; Ruminda Hutagalung; Nurhalimah; Emy Hariati; Hotman Efendi Tanjung (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the effect of the PBL (Problem-Based Learning) learning model on students' math arithmetical skills in integer material in class V of MIS Perdamean Sigambal, Rantauprapat, North Sumatra Province in the academic year 2020/2021. The research uses quantitative research (Quasi Experiment) with the research sample determined by total sampling technique. The population of the research was 30 students, which consists of 15 students in class V-A as the control class and 15 students in class V-B as the experimental class. The results indicate that students' arithmetic skills using the PBL learning model were in the very good category with an average score of 87.2. The hypothesis results that have been carried out indicate tcount 2.658 > ttable, 1.701 at a confidence level of 0.05. Thus, there is a significant effect of applying the PBL (Problem-Based Learning) learning model on students' arithmetical skills in class V of MIS Perdamean Sigambal Rantauprapat and it provides information to teachers in applying the PBL (Problem-Based Learning) learning model to improve students' thinking skills.